Natural bioactive compounds and their mechanisms of action in the management of obesity: a narrative review - Benbaibeche, Hassiba; Boumehira, Ali Zineddine; Khan, Naim Akhtar (Frontiers in Nutrition, 2025)
Obesity is a burning public health problem that affects both children and adult population all over the world. The incidence of obesity will increase in the coming years due to the urbanization of societies, which has led to unbalanced food intake and lack of physical activity among individuals. The efficacy of pharmaceutical interventions is limited, and a large number of drugs are known to trigger side effects, leading to their removal from the market. The use of natural products that exert least significant side effects can be a good alternative to prevent and manage obesity and its associated complications. These natural products include polyphenols, carotenoids and alkaloids that are recognized for their extensive range of biomedical applications and have been in practice for several decades. Administering low-to-moderate doses can yield a number of health benefits; thereby, enhancing their utility in clinical settings. Nevertheless, their direct application poses challenges due to several issues such as low bioavailability, scalability, environmental impact, clinical inconsistency, and toxicity at high doses. This review seeks to examine and identify the effects of some natural bioactive compounds (NBCs) in the management of obesity by targeting pathophysiological pathways, discuss the challenges associated with the use of NBCs including issues of bioavailability, dosage, toxicity and analysis of the efficacy of polyphenols in different models. It is necessary of address challenges associated with the use of NBCs by developing formulation strategies, establishing a safe concentration margin, employing humanized in vitro models to enhance translatability to clinical applications, optimizing dosage and harmonizing guidelines. The review also focuses on some conclusive studies demonstrating the potential anti-obesity effects of the most studied bioactive compounds in vitro, in vivo, and in clinical human trials through the regulation of appetite, adipogenesis, inflammation, thermogenesis and energy expenditure and gut microbiome.